Metal-organic frameworks with Lewis acidity: synthesis, characterization, and catalytic applications - Hu, Zhigang; Zhao, Dan (CrystEngComm, 2017)
Metal-organic frameworks (MOFs) are exquisitely architected through the pervasive coordination bonds between inorganic metal nodes and organic ligands. Marked by high porosity, tunable internal surface functionality, and concentrated metal sites, they are believed to act as the next generation adsorbent and catalytic materials. In particular, the presence of unsaturated metal centers and electron-deficient groups, capable of acting as Lewis acid sites, has made MOFs highly promising in heterogeneous catalysis applications. In this Highlight, we review the recent development in the design and synthesis of MOFs with Lewis acidity, the characterization techniques of Lewis acid sites, and their applications in heterogeneous catalysis. In this highlight, we review the recent development in the design and synthesis of metal-organic frameworks with Lewis acidity, the characterization techniques of Lewis acid sites, and their applications in heterogeneous catalysis.